2017
DOI: 10.1016/j.amjmed.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence of Hospitalized Acute Myocardial Infarction in the Cardiovascular Research Network (CVRN)

Abstract: Background Monitoring trends in cardiovascular events can provide key insights into the effectiveness of prevention efforts. Leveraging data from electronic health records provides a unique opportunity to examine contemporary, community-based trends in acute myocardial infarction hospitalizations. Methods We examined trends in hospitalized acute myocardial infarction incidence among adults aged ≥25 years in 13 U.S. health plans in the Cardiovascular Research Network. The first hospitalization per member for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 39 publications
6
45
0
3
Order By: Relevance
“…These findings seem to be in line with reported rates of CV events in the non-CAP population, with the exception of atrial fibrillation. Yearly trends in acute myocardial infarction show that hospital admission is decreasing in both the US and in Europe [5,98]. This may reflect the improved utilization of protective CV medication in the context of better primary care based prevention including pneumococcal and influenza immunization, along with improved secondary prevention after ACS.…”
Section: Discussionmentioning
confidence: 99%
“…These findings seem to be in line with reported rates of CV events in the non-CAP population, with the exception of atrial fibrillation. Yearly trends in acute myocardial infarction show that hospital admission is decreasing in both the US and in Europe [5,98]. This may reflect the improved utilization of protective CV medication in the context of better primary care based prevention including pneumococcal and influenza immunization, along with improved secondary prevention after ACS.…”
Section: Discussionmentioning
confidence: 99%
“…A number of community-based studies, including previous reports from the Worcester Heart Attack Study, 4,10,13,17 as well as large coronary disease registries, 18 have shown evidence of a progressive increase in the prescribing of effective cardiac therapies in patients hospitalized with AMI during the past 2 decades. Moreover, a gradual reduction in the utilization of cardiac medications with questionable therapeutic value or a narrow therapeutic/toxic ratio was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Opposite to health disparities, gender, age and genetics are a natural disorder cause. For example, a study by Reynolds et al (2016) found that women experienced a significantly greater decrease in incidence of myocardial infarctions compared with men. Other investigators suggest that cumulative stress may result in affecting biological processes, such as shortening telomere length.…”
Section: Health Disparitiesmentioning
confidence: 99%